Analisis Distribusi Ayam Broiler di Propinsi Daerah Istimewa Yogyakarta - Unggul Priyadi; Indah Susantun; Awan Setya Dewanta (Universitas Islam Indonesia, 2004)
Production of broiler chicken at Yogyakarta Province exceeds its consumption so that Yogyakarta province becomes one of suppliers of chicken for other regions, especially Jakarta. The objective of this research is to formulate distribution channel of broiler chicken, to determine transmission price elasticity and to estimate margin among distribution chan¬nels. The results show that pattern of production system consists of non-cooperative sys¬tem and cooperative (nucleus-core) system. Distribution channel of the non-cooperative system is more various than of that nucleus-core system. The margin of former system is also more efficient but more risky. Finally, producers are less responsive to price changes than distributors.Keywords: broiler chickens, distribusion channels, nucleus core system.